2021
DOI: 10.1002/adtp.202000259
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Extracellular Vesicles for Sepsis Treatment

Abstract: Sepsis is a deadly condition lacking a specific treatment despite decades of research. This has prompted the exploration of new approaches, with extracellular vesicles (EVs) emerging as a focal area. EVs are nanosized, cell-derived particles that transport bioactive components (i.e., proteins, DNA, and RNA) between cells, enabling both normal physiological functions and disease progression depending on context. In particular, EVs have been identified as critical mediators of sepsis pathophysiology. However, EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 425 publications
(643 reference statements)
0
11
0
Order By: Relevance
“…Further, there have been reports that the properties of MSC-derived EVs can be tuned with the culture environment of the cells [23,24]. EVs from MSC with three-dimensional (3D) cell aggregates (referred to as spheroids) exhibit not only high production yield but an enhanced expression of cytokines associated with immunosuppression and anti-apoptotic properties compared to conventional two-dimensional (2D) culture [25,26]. Moreover, it has been expected to release EVs with much higher similarity to in vivo circulating EVs due to the proximities of cell environments [27].…”
Section: Introductionmentioning
confidence: 99%
“…Further, there have been reports that the properties of MSC-derived EVs can be tuned with the culture environment of the cells [23,24]. EVs from MSC with three-dimensional (3D) cell aggregates (referred to as spheroids) exhibit not only high production yield but an enhanced expression of cytokines associated with immunosuppression and anti-apoptotic properties compared to conventional two-dimensional (2D) culture [25,26]. Moreover, it has been expected to release EVs with much higher similarity to in vivo circulating EVs due to the proximities of cell environments [27].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are natural carriers for plasma miRNAs ( Thery et al., 2002 ). Our recent work has revealed that miR-146a-5p expression is upregulated in septic plasma EVs and may contribute to the proinflammatory effect of septic EVs ( Kronstadt et al, 2021 ; Xu et al., 2018 ). Indeed, HEK293T EVs loaded ss miR-146a-5p mimics induced a robust CXCL2, TNFα, and IL-6 production in BMDMs ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
“…Research of endogenous EVs and their specific roles in sepsis progression reveal numerous diagnostic capabilities in pre-clinical sepsis models, as well as in human patients [56]. As mentioned above, EVs plasma levels in general have been proposed as predictive biomarkers for organ failure and mortality rate of septic patients [22], as well as, specific miRNA expression profile in EVs from septic patients, that has been also associated with sepsis survival and disease stage [57].…”
Section: Evs As Diagnostic Markersmentioning
confidence: 99%